2005
DOI: 10.1088/0953-8984/17/37/009
|View full text |Cite
|
Sign up to set email alerts
|

The macroscopic symmetry of Pb(Mg1/3Nb2/3)1−xTixO3in the morphotropic phase boundary region (x= 0.25–0.5)

Abstract: The macroscopic symmetry of Pb(Mg1/3Nb2/3)1−xTixO3 (PMN–PT) crystals with x = 0.25–0.5 has been studied by optical microscopy. Precise data on the temperature dependence of the birefringence and optical extinction directions have been obtained. Two different low-symmetry phases separating rhombohedral and tetragonal phases have been observed in the compositional range x = 0.3–0.47. The optical extinction in the range x = 0.3–0.37 is consistent with Cm space group symmetry, while for x = 0.37–0.47 Pm symmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 32 publications
3
51
1
Order By: Relevance
“…In the case of the PMN-29%PT the Noheda' phase diagram [11] does not show such phase transition. However, recently some articles appears in which additional phase transition was observed in the solid solutions with similar compositions: 27%PT and 29%PT [13,16,17] and interpreted as structural phase transitions from the monoclinic (Cm or Pm space group) to the rhombohedral symmetry. Moreover, even presence of structural phase transitions between two different monoclinic symmetry and/or the coexistence of the phases (two monoclinic or rhombohedral-monoclinic) were suggested [13,17] …”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the PMN-29%PT the Noheda' phase diagram [11] does not show such phase transition. However, recently some articles appears in which additional phase transition was observed in the solid solutions with similar compositions: 27%PT and 29%PT [13,16,17] and interpreted as structural phase transitions from the monoclinic (Cm or Pm space group) to the rhombohedral symmetry. Moreover, even presence of structural phase transitions between two different monoclinic symmetry and/or the coexistence of the phases (two monoclinic or rhombohedral-monoclinic) were suggested [13,17] …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…According to the X-ray diffraction the high temperature symmetry is cubic with the Pm3m space group [9][10][11][12][13][14][15][16][17][18]. As we already mentioned for such symmetry the first order Raman activity is forbidden.…”
Section: Temperature Evolution Of the Fwhms And Intensitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Coexistence of different phases is rather frequent phenomenon in case of first-order phase transformations and a planar macroscopic phase front can be stabilized for example with the aid of temperature or concentration gradient. 26 Macroscopic phase boundary between different ferroelectric phases has been previously observed in PMN-xPT crystal with a linear gradient of Ti concentration 27 . However, in that work, the phase boundary seems to simply delimit Ti-poorer regions from Ti-richer regions, without any obvious relation to the crystallographic orientation of the sample.…”
mentioning
confidence: 81%
“…This is in good agreement with previous reports, in which only the M A phase was observed at low temperature. 27 Such phase transition is expected to relate to the nanoinhomogeneous, i.e., PORs or CORs, in the crystal. It has been indicated that the M C -M A phase transition under external electric field arises from the polarization switching mechanism.…”
mentioning
confidence: 99%